Faithless Justice: Understanding the Justice System’s Role in Facilitating Abuse of the Blasphemy Laws in Pakistan. - Jafri, Faryal Z. (Tufts Archival Research Center, 2018)
While the blasphemy laws in Pakistan were ostensibly intended to protect religious sentiments, they have transformed into a tool of violence in recent years. Since the 1980s, the number of blasphemy cases and accusations has skyrocketed. In this paper, I argue that this dramatic rise in cases is due to increased abuse of these laws, facilitated by flaws in the justice system. Ultimately, I contribute to literature on the blasphemy laws in Pakistan by pointing specifically to their implementing systems as responsible for their abuse. I further demonstrate how flaws in this system have given rise to the informal justice system that has resulted in a general reduction of security for many Pakistani citizens.